Molecular Rearrangement of Pyrazino[2,3-c]quinolin-5(6H)-ones during Their Reaction with Isocyanic Acid - Klásek, Antonín; Lyčka, Antonín; Křemen, Filip; Růžička, Aleš; Rouchal, Michal (International journal of molecular sciences, 2022)
New tetrahydropyrazino[2,3-c]quinolin-5(6H)-ones were prepared from 3-chloroquinoline-2,4(1H,3H)-diones and ethylene diamine. In their reaction with HNCO, an unprecedented molecular rearrangement produced new types of hydantoin derivatives. All prepared compounds were characterized on the basis of their 1H, 13C, and 15N NMR and ESI mass spectra and some were authenticated by X-ray analysis of single crystalline material. A proposed mechanism for rearrangement is discussed in this essay. The CDK and ABL inhibition activity as well as in vitro cytotoxicity of the prepared compounds was also tested.
Keywords: scXRD; 1H-, 13C- and 15N-NMR; kyanatany; 4-alkylidene-1’H-spiro[imidazolidine-5,3’-indole]-2,2’-diones; Magnetic Resonance Spectroscopy; 3-(3-acylureido)-2,3-dihydro-1H-indol-2-ones; Cyanates; magnetická rezonanční spektroskopie; imidazo[1,5-c]quinazoline-3,5-diones; biological activity